2004
DOI: 10.1021/np030530j
|View full text |Cite
|
Sign up to set email alerts
|

Benzoic Acid Derivatives from Piper Species and Their Fungitoxic Activity against Cladosporium cladosporioides and C. sphaerospermum

Abstract: Piper crassinervium, P. aduncum, P. hostmannianum, and P. gaudichaudianum contain the new benzoic acid derivatives crassinervic acid (1), aduncumene (8), hostmaniane (18), and gaudichaudianic acid (20), respectively, as major secondary metabolites. Additionally, 19 known compounds such as benzoic acids, chromenes, and flavonoids were isolated and identified. The antifungal activity of these compounds was evaluated by bioautographic TLC assay against Cladosporium cladosporioides and C. sphaerospermum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
120
0
28

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 191 publications
(153 citation statements)
references
References 27 publications
5
120
0
28
Order By: Relevance
“…Phytochemical investigations of Piper species have led to the identification of typical classes of compounds such as amides, terpenes, benzoic acid derivatives, carotenes, and hydroquinones in addition to lignans, neolignans and a few alkaloids (Navickiene et al, 2000;Silva et al, 2002;Lago et al, 2004;Navickiene et al, 2006;Potzernheim et al, 2006;Regasini et al, 2008;Continguiba et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical investigations of Piper species have led to the identification of typical classes of compounds such as amides, terpenes, benzoic acid derivatives, carotenes, and hydroquinones in addition to lignans, neolignans and a few alkaloids (Navickiene et al, 2000;Silva et al, 2002;Lago et al, 2004;Navickiene et al, 2006;Potzernheim et al, 2006;Regasini et al, 2008;Continguiba et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Piper species have revealed the presence of several classes of secondary metabolites, 1 including alkaloids, amides, 2-6 chromenes, 7,8 neolignans, 9 lignans, terpenes, 10,11 benzoic acid derivatives 12,13 and kavalactones.…”
Section: Introductionmentioning
confidence: 99%
“…Local communities have traditionally used this species as an anesthetic sedative for toothache, antidote for snake bite, stimulants, and stomach problems (Chaves et al, 2003). Recent studies showed that different extracts and isolated molecules from P. tuberculatum present antifungal (Lago et al, 2004), antitumor (Bezerra et al, 2006), antiplatelet aggregation (Fontenele et al, 2009), insecticide (Pohlit et al, 2004) and hypotensive properties (Duarte et al, 2004).…”
Section: Introductionmentioning
confidence: 99%